Study on external corrosion dynamic of buried steel coupons - Lee, Yeong Huei, 1985-; Norhazilan Md. Noor, supervisor; Fakulti Kejuruteraan Awam (2010)
Project Paper (Sarjana Muda Kejurteraan Awam) - Universiti Teknologi Malaysia, 2010